Silencing of Adc and Ebony Causes Abnormal Darkening of Cuticle in Henosepilachna vigintioctopunctata - Ze, Long-Ji; Jin, Lin; Li, Guo-Qing (Frontiers in Physiology, 2022)
N-β-alanyldopamine (NBAD) is one N-acylquinone sclerotin utilized for cross-linking between cuticular proteins for cuticle during insect molting. The importance of NBAD in cuticle tanning has not been well compared among different developing stages of insects. Henosepilachna vigintioctopunctata, a typical polyphagous pest feeding on a large number of Solanaceae and Cucurbitaceae plants in Asian countries, displays diverse cuticle pigmentation pattern among developing stages and body regions. Here, we found that the expression of three genes (Hvadc, Hvebony and Hvtan) involving in NBAD biosynthesis peaked in the 4-day-old pupae or 0-day-old adults of H. vigintioctopunctata. At the first-, second-, third-, and fourth-larval instar and pupal stage, their transcript levels were high just before and/or right after the molting. Moreover, they were more abundantly transcribed at the larval heads than in the bodies. RNA interference (RNAi) of either Hvadc or Hvebony at the third instar larvae selectively deepened the color of the larval head capsules, antennae, mouthpart, scoli, strumae and legs; and depletion of the two genes blackened the pupal head capsules, antennae, mouthpart and legs. However, knockdown of either Hvadc or Hvebony darkened whole bodies of the adults. Conversely, RNAi of Hvtan at the third instar stage had little influence on the pigmentation in the larvae, pupae and adults. These findings demonstrated that Adc and Ebony are important in cuticle pigmentation of H. vigintioctopunctata and suggested that larger quantities of NBAD were present in adults and play more important roles in pigmentation than larvae/pupae.